Inferior parietal lobule is sensitive to different semantic similarity relations for concrete and abstract words. (19th December 2020) - Montefinese, Maria; Pinti, Paola; Ambrosini, Ettore; Tachtsidis, Ilias; Vinson, David
Abstract: Similarity measures, the extent to which two concepts have similar meanings, are the key to understand how concepts are represented, with different theoretical perspectives relying on very different sources of data from which similarity can be calculated. While there is some commonality in similarity measures, the extent of their correlation is limited. Previous studies also suggested that the relative performance of different similarity measures may also vary depending on concept concreteness and that the inferior parietal lobule (IPL) may be involved in the integration of conceptual features in a multimodal system for the semantic categorization. Here, we tested for the first time whether theory‐based similarity measures predict the pattern of brain activity in the IPL differently for abstract and concrete concepts. English speakers performed a semantic decision task, while we recorded their brain activity in IPL through fNIRS. Using representational similarity analysis, results indicated that the neural representational similarity in IPL conformed to the lexical co‐occurrence among concrete concepts (regardless of the hemisphere) and to the affective similarity among abstract concepts in the left hemisphere only, implying that semantic representations of abstract and concrete concepts are characterized along different organizational principles in the IPL. We observed null results for the decoding accuracy. Our study suggests that the use of the representational similarity analysis as a complementary analysis to the decoding accuracy is a promising tool to reveal similarity patterns between theoretical models and brain activity recorded through fNIRS. Abstract : Our findings provide direct evidence that the inferior parietal lobule represents distributional and affective information depending on the word concreteness, implying that semantic representations of abstract and concrete concepts are characterized along different organizational principles. We also complemented previous evidence further charactering the role of the inferior parietal lobule in semantic processing.